KONSEP PENDIDIKAN ISLAM DALAM MEMBINA AKHLAK TERHADAP ANAK - Indah Sari, Nur (AS-SALAM, 2015)
The concept of Islamic education in fostering the morals of the childrenhad a great influence on a system of Islamic education, so that informulating the concept of Islamic education takes the basics of theQuran and al-Hadith. Coaching morals of children may be interpretedto foster behavior that can lead to good and evil. Personal generallyhave elements of both mind and body are mutually reinforcing unitybetween one another and can not be liberated and is a human childor a person of immature, gift and a deposit which must be maintainedas well as the mandate for the adults, especially the elderly whereparents also have a responsibility to the children in many ways, goodmaintenance, education, development and future.The purpose of this study was to determine the basis and purposeof fostering the morals of children and to determine the method infostering the morals of children. Based on these results, the authorsconclude that the concept of Islamic education is an importantfoundation in mebina morals of children, where the concept of Islamiceducation there is a strong foundation namely the Quran and AlHadith which will print the child becomes human being virtuousand praiseworthy morals. Factors that play a role in influencingthe formation and moral development of children include internalfactors and external factors, including heredity, age, personality, andpsychological condition of a person and of the environment in whichone lives. Generally, the neighborhood is divided into three, namely:family, institution, community.Keywords: The Concept of Islam Education, Morals Promoting ofChildren.